Peltobiomassat tulevaisuuden energiaresurssina - Pahkala, Katri (toim.); Lötjönen, Timo (toim.) (MTT, 2012)
Biomassoja voidaan tuottaa varta vasten bioenergiaksi tai ne voivat olla sivuvirtoja puunjalostusteollisuudesta, maa- ja metsätaloudesta tai esimerkiksi yhdyskuntajätteen biohajoavan osan hyödyntämistä energiaksi. Pohjoismaissa ja Venäjällä metsä on luontainen bioenergian lähde, mutta monissa muissa maissa metsiä on hyvin vähän. Siten peltojakin kannattaa tarkastella bioenergian tuottajina. Bioenergiakasvien tuottamista pellolla on kuitenkin arvosteltu siitä, että maailman ruokahuolto ei ole tällä hetkelläkään optimaalinen, ja maailman väkiluvun kasvaessa yhä enemmän peltoalaa tarvittaisiin ruoan tuotantoon, jolloin bioenergian tuotanto kilpailisi ruoantuotannon kanssa sosioekonomisesti kestämättömällä tavalla. Tässä tutkimuksessa tarkasteltiin Euroopan maiden peltobiomassapotentiaaleja erilaisilla skenaario-oletuksilla sekä selvitettiin kestävän kehityksen mukaista peltobioenergian tuotantoa. Tutkimuksessa keskityttiin erityisesti ruoantuotannon, väkiluvun kasvun, maatalouden kehittymisen ja ilmastonmuutoksen vaikutuksiin alueellisiin peltoviljelystä saataviin bioenergiapotentiaaleihin. Bioenergiakasvien tuotantoon ruuan tuotannon jälkeen jäävä peltopinta-ala riippuu eniten ihmisten ruokavaliosta. Kasvisruokavalio säästäisi niin paljon viljelyalaa, että suurin osa tutkimuksessa olevista maista pystyisi jo tällä hetkellä viljelemään bioenergiakasveja yli puolella peltoalastaan hyvän kehityksen skenaariossa. Huonon kehityksen skenaariossa kasvisruokavalio ei enää vapauttaisi viljelyalaa kaikissa maissa. Sekaruokavalion vaikutus on dramaattinen: hyvänkin kehityksen skenaariossa suurimmalla osalla tutkituista maista bioenergian tuotantoon voitaisiin käyttää alle puolet peltoalasta eikä useissa maissa bioenergian tuotantoon jäisi ollenkaan peltoalaa. Lihapitoisella ruokavaliolla peltoa jäisi bioenergiantuotantoon vain harvassa maassa. Tulevaisuudessa tilanne saattaa parantua bioenergian tuotannon kannalta, kun teknologian ja kasvinjalostuksen kehitys lisäävät satoja etenkin entisen Neuvostoliiton maissa. Joissakin maissa, kuten Pohjois-Euroopassa, myös ilmastonmuutos vaikuttaa satoihin myönteisesti, mikäli muutos ei etene liian voimakkaasti. Samalla useimpien nyt tarkasteltujen maiden väkiluku nousee vain vähän, mikä osaltaan vapauttaa peltoja ruoantuotannosta. Peltokasvien sivutuotteet eivät sovellu ihmisten ravinnoksi ja niiden rehukäyttökin on rajallista, joten tässä mielessä ne joutavat hyvin biojalostamojen raaka-aineiksi tai polttoaineeksi energiantuotantoon. Peltokasvien sivutuotteiden potentiaalista valtaosa, 70-90 %, koostuu kaikissa tarkastelluissa maissa viljakasvien oljista. Suurimmat sivutuotemäärät löytyvät Länsi-Euroopassa suuruusjärjestyksessä Ranskasta, Saksasta, Iso-Britanniasta, Italiasta ja Espanjasta. Itä-Euroopassa suurimpia tuottajia ovat Venäjän Euroopan puoleiset osat, Ukraina ja Puola. Ukrainan ja Venäjän nyt suhteellisen heikkojen satojen arvellaan kasvavan tulevaisuudessa nopeasti. Pohjoismaissa suurin sivutuotemäärä muodostuu Tanskassa. Merkittävin rajoittava tekijä sivutuotteiden hyödyntämisessä on pellon kasvukunnon säilyttäminen. Tässä tutkimuksessa oletettiin 50 % kasvijätteestä jäävän vuosittain pelloille multavuutta parantamaan. Arvioon sisältyy kuitenkin suurta epävarmuutta alueittain ja maalajeista johtuen. Vähintään 20-30 % vuosittain muodostuvasta sivutuotteen määrästä olisi teknis-taloudellisesti käytettävissä bioenergiaksi. Euroopan suurissa maatalousmaissa tämä tarkoittaa 20-75 TWh:n teknis-taloudellista energiapotentiaalia. Suomessakin peltojen sivutuote-energialla (noin 2,4 TWh) voi olla merkitystä etenkin hajautetussa energiantuo-tannossa ja myös keskitetyssä tuotannossa muiden uusiutuvien energiamuotojen tukena. Nurmialueiden käyttöä bioenergian tuottamiseen tarkasteltiin erikseen. Nurmien käyttöön vaikuttavat olennaisesti nurmirehua käyttävien eläinten lukumäärät ja viljarehun hinta. Euroopassa nurmirehua käyt-tävien eläinten määrä on vähentynyt, ja nurmibiomassaa olisi käytettävissä energian tuotantoon. Jos vilja-väkirehun hinta nousee voimakkaasti, se lisää kiinnostusta nurmirehun osuuden kasvattamiseen karjan ruokinnassa ja silloin bioenergiaksi käytettävissä olevan nurmirehun määrä vähenee. Suomessa olisi mahdollista käyttää erilaisilta kesantopelloilta saatavaa nurmibiomassaa energian tuotantoon, tämä muo-dostaa merkittävän potentiaalin. Nurmibiomassa voitaisiin varastoida säilörehun tapaan ja tehdä siitä bio-kaasua. Myös rehunurmien vuosittaisen satovaihtelun vuoksi nurmibiomassaa olisi käytettävissä energi-antuotantoon. Nurmibiomassaa olisi saatavissa kohtuullisen pieniltäkin alueilta riittävästi suhteellisen kookkaiden 3-4 MW biokaasulaitosten tarpeisiin. Riittävän massan tuottamiseen tarvittava nurmiala olisi noin 1000 ha, kun nurmen viljely olisi intensiivistä ja hehtaarisato 7 500 kg ka/ha.

Bioenergy can be derived from biomasses especially produced for bioenergy or from by-products, side streams and waste from wood processing industry, agriculture and forestry, or e.g. municipal waste. In the Nordic countries and Russia forests are a natural source of bioenergy. In many other European countries forests may be too scarce for bioenergy use. Therefore field biomasses form an interesting potential source for bioenergy. Production of field biomasses for non-food purposes has been criticized, especially as there is not enough food for everyone even at present, and in the future more food has to be produced as the world population increases. We studied the field biomass potential in different European countries with different scenarios for develop-ment. "Good development" scenario includes improvements in plant breeding and food production and pro-cessing technologies, with increasing yields and decreasing waste of food products and raw materials. "Bad development" scenario assumes stagnating yields and little improvement in technologies in the OECD coun-tries, and only small improvements in former Soviet Union countries. The foci of the present research were the effects of development of food production, population growth and climate change on regional potential of field biomasses for bioenergy and sustainable use of crop residues and grasses for bioenergy. The field area that could be allocated to energy crops after growing enough food for the citizens of each country depends mostly on the diet. Growing food for vegetarian diet would occupy so little field area that every country under study could set aside at least half of their field area for bioenergy purposes already at present, if the "good development" scenario was applied. With "bad development" scenario some of the countries would be unable to set aside fields for bioenergy production even with vegetarian diet. With affluent diet there would be little field area left over for energy crops, and already with mixed diet even with the "good development" scenario, less than half or even none of the field area could be allocated to energy crops in many of the studied countries. In the future the situation may become more favorable for production of biomasses for energy, if plant breeding is successful and also cultivation and procession technologies proceed favorably. In some countries, especially in the north, also climate change may increase production potential. At the same time, the population may not increase much in the countries studied here, which together with favorable development may free field area from food production. Residues of field crops unsuitable for food or fodder could be used as raw material for bioenergy. The largest available source (70-90%) of potential field crop residue material is straw of cereals. The biggest producers of cereals and thus straw for bioenergy are (in order of production quantity) France, Germany, Great Britain, Italy and Spain in Western Europe and Russia (European part), Ukraine and Poland in Eastern Europe. The presently quite modest yields and thus bioenergy potential of cereal straw of Ukraine and Russia are expected to increase considerably in the near future. In the Nordic countries, the largest field crop residue potential is in Denmark. A major constraint in adopting usage of straw material for bioenergy is the maintenance of soil organic matter and productivity. In the present study we assumed that 50% of the potential straw biomass was left in the field to improve soil quality. Differences in growth conditions, soil quality and soil type and texture complicate estimates of residue potential, but on general at least 20-30% of the potential straw residue could be used for bioenergy. In the big agricultural countries in Europe this would translate into 20-75 TWh of technically available and economically feasible bioenergy potential annually. Also in Finland, field residue material could be an important source of bioenergy, especially in regional energy industry, but also in centralized production together with other sources of renewable energy. The usage of bioenergy could increase more rapidly if it was economically feasible for both the farmers, transport companies and end users of the raw materials. Production of bioenergy could be increased by plant breeding and improved technology. Unfortunately the production of bioenergy from field biomasses requires its own production chains, as it has been shown not to be suitable for the existing energy peat or wood production chains. In addition, economical incentives are needed, such as viable emission trade system or feed-in tariff for biomass-derived energy, already now in use in Germany and Austria. Even though the EU has a common agricultural and energy policy, national decisions can make a difference in which form of energy is profitable for producers. The usage of grassland biomasses for bioenergy was studied separately. Potential of grassland biomasses as energy source is affected by the number of cattle and price of fodder grain. In Europe the number of animals using grass fodder has decreased, and there would be more grass material available for bioenergy production. However, if the price of grain based fodder increases heavily, the interest to use more grass based fodder may increase and then the potential of grass for bioenergy decreases. In Finland a significant unused potential is the plant biomass derived from different kinds of fallow. Biomasses from the fallows could be stored as silage and fermented for biogas. The yearly yield fluctuations of grass may also allow usage of surplus grass for bioenergy. Grass biomass could be collected from reasonably small areas to satisfy the needs of even rather big biogas plants.
Keywords: Ka; bioenergia; peltokasvit; biomassa; energiapotentiaali; olki; ruoantuotanto; bioenergy; biomass; by-products; crop residues; field bioenergy potential; straw; food production; grassland; biogas